Keberhasilan Keberhasilan Layanan Pajak Online Terhadap Optimalisasi Penerimaan Pajak Daerah di Kota Metro - fitri wahyu niarseh; Nana Mulyana; Yulianto Yulianto (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2026)
The problem of regional tax management in Metro City is evident in the low compliance of PBB-P2 taxpayers who still rely on manual payments and the minimal socialization of digital services. This condition has resulted in tax revenue not meeting targets despite increasing numbers every year. In response to this problem, the Metro City Regional Tax Office (BPPRD) introduced an online tax service to simplify the reporting and payment process. This study aims to assess the service's success, supporting factors, and obstacles to its implementation using qualitative methods through interviews, observation, and documentation. The results show that online tax services can increase access and accelerate payments, but are not yet fully effective in encouraging regional tax optimization. Supporting factors include local government policy support, digital system readiness, and the BPPRD's commitment to encouraging the use of online services. Meanwhile, the main obstacles stem from a lack of socialization, limited digital literacy among the community, technical glitches, and information delivery that has not yet reached neighborhood units (RTs), resulting in uneven use of the service. Therefore, it is necessary to expand socialization, strengthen digital education, and improve system stability so that online tax services can function more optimally and contribute to regional tax revenue.